Nobody can Really Afford Legal Services: The Price of Justice in Namibia - Zongwe, Dunia (Potchefstroom Electronic Law Journal, 2021)
Nobody (except for the privileged few) can afford legal services in Namibia. In the light of this dawning awareness, how should the government and other stakeholders design the legal profession so that the greatest number of Namibians can access legal services and, ultimately, justice while preserving the profession’s financial viability? The predominantly economic nature of this question means that its solutions lie less in the field of law than in the field of economics. Thus, this article adopts a methodology that reflects that insight. As a primary purpose, this article works towards solving the high cost of legal services in Namibia. It utilises a literature-review methodology that searches the scholarship on the legal profession for practical, down-to-earth solutions put forward in other countries to take the edge off the prohibitive cost of legal services. The article mainly finds that, if structured as a compulsory salary deduction, legal insurance promises the greatest positive impact on costs. And it concludes that the optimal solutions should consist of measures aimed at heightening competition in the legal profession and measures that broaden cost-sharing in providing legal assistance to the public. The article argues that competition can be effectively increased by lubricating the flow of information about prices and services, and by having more public entities bear the burden of expanding the system of legal assistance.